A study of Cicadellidae Populations on Andropogon virginicus and Dactylis glomerata in Frederick County, Maryland - Hoover, Barbara Kristin (My University, 1980)
Cicadellidae cause serious economic damage as a result of both their feeding on valuable farm crops and through the viruses that they transmit to those crops. In order to study this problem, collections of leafhoppers were made on Andropogon virginicus and Dactylis glomerata using a D-VAC(R) vacuum net sampling device. Temperature, wind speed, and wind direction data were collected from a weather station operated at Ft. Detrick in Frederick, Maryland. Collections of leafhoppers were made on a weekly basis over a five and one-half month period during the summer and fall of 1978 in Frederick County, Maryland. Specimens found in these collections were asphyxiated with ethyl acetate and identified to species level if possible. Population fluctuations of each species were examined. On the basis of high population levels and the potential for virus transmission, Endria inimica, Graminella nigrifrons, Stirellus bicolor, Psammotettix sp., Draeculacephala portola and Aphrodes sp. were identified as the species most capable of causing economic damage to valuable crops. Temperature and wind speed were found to influence the number of leafhoppers collected in a sample. Wind direction was not considered to be a factor in the number collected. Suggestions for using the information contained in this paper in a program of integrated pest management are presented.